Pengembangan Kompetensi Siswa SMK Melalui Model Teaching Factory : Peran Teaching Factory Dalam Menyiapkan Tenaga Kerja Terampil - Aropah, Siti; Kurniawan, Rezha Aji; Yayuk, Erna (Universitas Hamzanwadi, 2026)
In the world of the industry, skilled labor is the main factor in increasing the competitiveness of companies, so the teaching factory concept is present as a solution to equip students with practical skills that suit the needs of the industry. This study aims to describe the implementation of the Teaching Factory model at SMK Muhammadiyah 6 Rogojampi and its role in preparing a skilled workforce that is in accordance with the needs of the industry. The research method used was qualitative descriptive with data collection techniques through interviews, observations, and documentation. The research subjects include school principals, productive teachers, students majoring in Computer and Network Engineering (TKJ), and industrial partners. The results of the study show that the implementation of the Teaching Factory at SMK Muhammadiyah 6 Rogojampi includes curriculum alignment, real projects, and evaluation of students' work, which is effective in improving skills and work ethic. However, challenges such as lack of sustainable projects and differences in student competencies still occur. Even so, Teaching Factory has been proven to increase job readiness if supported by industry partnerships and flexible learning strategies.